2020
DOI: 10.1097/hcr.0000000000000525
|View full text |Cite
|
Sign up to set email alerts
|

Muscular Strength and Cardiovascular Disease

Abstract: This review discusses the associations of muscular strength (MusS) with cardiovascular disease (CVD), CVD-related death, and all-cause mortality, as well as CVD risk factors, such as metabolic syndrome, diabetes, obesity, and hypertension. We then briefly review the role of resistance exercise training in modulating CVD risk factors and incident CVD. The role of MusS has been investigated over the years, as it relates to the risk to develop CVD and CVD risk factors. Reduced MusS, also known as dynape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(58 citation statements)
references
References 98 publications
1
44
0
Order By: Relevance
“…In the present study, hypertension and obesity were confirmed as the predictors of intention to engage in muscle training in at-risk CVD groups. As emphasized by the AHA guidelines [ 19 ], with the importance of muscle training in preventing CVD and in lowering the associated mortality, muscle training becomes more important with advancing age [ 32 ]. Our results showed that only 20.3% of the intermediate-risk group and 24.9% of the high-risk group engaged in muscle training, hence highlighting the importance of strategies that instill self-efficacy and inform individuals about the outcomes of exercise, for example it is recommended, to promote muscle training [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, hypertension and obesity were confirmed as the predictors of intention to engage in muscle training in at-risk CVD groups. As emphasized by the AHA guidelines [ 19 ], with the importance of muscle training in preventing CVD and in lowering the associated mortality, muscle training becomes more important with advancing age [ 32 ]. Our results showed that only 20.3% of the intermediate-risk group and 24.9% of the high-risk group engaged in muscle training, hence highlighting the importance of strategies that instill self-efficacy and inform individuals about the outcomes of exercise, for example it is recommended, to promote muscle training [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…as numerous studies have reported their overall benefits, 20 21 especially in older and clinical populations. [22][23][24][25] For example, handgrip strength was demonstrated to be the third strongest modifiable risk factor for mortality when considered together with other behavioural, metabolic, socioeconomic and psychosocial factors, household and ambient pollution. 26 Notably, it was found out that muscle power is a stronger predictor of functional ability in older people than muscle strength, muscle mass and aerobic capacity.…”
Section: Original Researchmentioning
confidence: 99%
“…Handgrip strength measured by dynamometry has been used as an isolated surrogate marker for muscle strength and frailty [29], and it has been associated with higher postoperative complication rates and increased mortality in patients with advanced CHF undergoing LVAD implantation [44]. There are also numerous bioelectrical and imaging methods that have been used to assess body composition indirectly in the context of CHF, including bioelectrical impedance analysis (BIA), Dual Energy X-Ray Absorptiometry (DXA), computed tomography (CT), magnetic resonance imaging (MRI) and muscle ultrasound.…”
Section: Anthropometry and Body Composition Evaluationmentioning
confidence: 99%
“…It has been shown that in patients undergoing LVAD implantation or after cardiac transplantation, sarcopenia, as measured by psoas muscle area, is associated with major morbidity and increased mortality [27,28]. However, it is not clear whether reduced muscle strength is a mediator or simply a marker of worse nutritional status related to a greater risk of cardiometabolic diseases [29]. Thus, current evidence suggests that CHF is associated with alterations in energy metabolism at the myocardial level, which influences the nutritional state.…”
Section: Introductionmentioning
confidence: 99%